STRUKTUR DAN INTEGRASI PASAR EKSPOR LADA HITAM DAN LADA PUTIH DI DAERAH PRODUKSI UTAMA - ADIMESRA DJULIN; A. HUSNI MALIAN (SOCA: Jurnal Sosial Ekonomi Pertanian, 2005)
Pepper agribusiness in Indonesia has contributed to farmer’s incomegeneration and national foreign exchange earnings. Most pepper exportdestination is Singapore or United States of America. Annual growth rate ofpepper export value during 1989-1998 was 9.0%, although there was adecrease in 2001. The objective of the study is to identify pepper marketstructure and integration in Indonesia. Selected study sites are main productioncenters which are Lampung Province for black pepper and Bangka-BelitungPropince for white pepper. Various primary and secondary data had beencollected from various sources. An analysis model of market integration ofmodified Ravallion Model (1986) was applied. The result shows that blackpepper farm gate price is not integrated with exporter’s gate price, while theexporter’s gate price and the world’s price is weakly integrated. In addition,white pepper farm gate price is integrated very weakly with exporter’s gateprice; in contrast the exporter’s gate price is strongly integrated with the world’spepper price. This strong integration reflects that domestic price movement isheavily affected by international price fluctuation. This indicates that peppercommodity development should take efficiency and world marketcompetitiveness into consideration.